Sr immobilization in irradiated Portland cement paste exposed to carbonation. (May 2018) - Bar-Nes, Gabriela; Klein-BenDavid, Ofra; Chomat, Laure; Macé, Nathalie; Arbel-Haddad, Michal; Poyet, Stéphane
Abstract: Cement based materials are widely used as binding matrices for radionuclides in low and intermediate level waste management applications. We studied the effect of irradiation and carbonation under atmospheric condition on the leaching of Sr from Portland cement paste. Samples were exposed to gamma irradiation or subjected to thermal treatment under either inert or atmospheric conditions. Leaching tests were performed and supplemented by post-leaching characterization including local chemical analysis (LA-ICPMS) crystallographic analysis (XRD), and EPMA imaging. The combination of these methods enabled us to link between the crystallography, texture and composition of the treated samples and their ability to retain Sr ions. Results show that carbonation was the main factor determining the retention of Sr ions, whereas irradiation did not have a significant effect. Moreover, carbonation has a positive effect on the retention of Sr ions in the matrix with the formation of a carbonated zone.